Synthesis of novel functionalized dihydroimidazo[2, 1-a]isoquinolines and dihydroimidazo[2, 1-a] quinolines: single crystal X-ray studies of (Z)-methyl 2-(1-(benzo[d]thiazol-2-yl)-2-oxo-1, 2-dihydroimidazo[2, 1-a]isoquinolin-3(10bH)-ylidene)acetate. Issue 8 (25th February 2015) - Arab-Salmanabadi, Samira; Dorvar, Marzieh; Notash, Behrouz
Abstract: A series of novel functionalized dihydroimidazo[2, 1- a ]isoquinolines and dihydroimidazo[2, 1- a ] quinolines were synthesized via the reaction between isoquinoline or quinoline derivatives and dialkyl acetylenedicarboxylates in the presence of 2-aminobenzothiazole in excellent yields. These novel synthesized compounds were suitably characterized by elemental analysis, Mass spectroscopy, IR, 1 H-NMR & 13 C-NMR spectra. In addition the compound ( Z )-methyl 2-(1-(benzo[ d ]thiazol-2-yl)-2-oxo-1, 2-dihydroimidazo[2, 1- a ]isoquinolin-3(10b H )-ylidene)acetate was subjected to the single crystal X-ray diffraction studies. Graphical abstract: